Estudo do tempo de instalação da neurite óptica como fator preditivo de incapacidade funcional no espectro da neuromielite óptica. - Juliana Machado Santiago Santos Amaral (2020)
Neuromyelitis optica spectrum disorders (NMOSD) is a severe inflammatory disease of the central nervous system most frequently related to aquaporin 4 autoimmunity. Optic neuritis (ON) is one of the three most characteristic syndromes of NMOSD and occurs in over one half of the patients at disease onset. As NMOSD is an unpredictable and severe disease, identification of prognostic factors is of utmost importance. This thesis comprises two distinct but complementary studies. The first study, entitled Optic neuritis at onset predicts poor visual outcome in neuromyelitis optica spectrum disorders, is a longitudinal observational study that analyzes ON at disease onset and in the course of NMOSD, correlating the time of event occurrence with prognosis. We analyzed the medical records of a cohort of 85 patients with ON in NMOSD. Patients were separated in three groups. Patients who presented ON only at disease onset (n = 16); who did not have ON at disease onset but presented it in the posterior course of the disease (n = 43); and patients who presented ON both at disease onset, and later during the course of the disease (n = 26). Demographic, clinical data and disability scores at last follow up were assessed. Expanded Disability Status Scale (EDSS), Kurtzke's Visual Functional System (KVS) and Wingerchuk’s Optic Nerve Impairment Scale (WONIS) were used to measure disability. Covariance analysis considering possible confounding factors in the prognosis, showed that patients who started the disease with ON had a more severe visual outcome than patients who manifested this symptom only later on, in the course of the disease. Still more severe disability ensues relapsing ON in those patients. The second study, Isolated optic neuritis at the onset of neuromyelitis optica spectrum disorders is a predictive factor of poor visual outcome, is also a longitudinal observational study that compares the outcome of NMOSD in patients with isolated ON at disease onset with that of patients whose ON at disease onset occurred in association with other neurological symptoms. We analyzed the medical records of a cohort of 42 NMOSD patients and ON at disease onset. The cohort was divided into two groups. The first group comprised 30 patients who presented isolated ON as the inaugural symptom of the disease. The second group (n = 12) comprised patients who had ON associated with other neurological symptoms at disease onset. The demographic, clinical data and disability scores at last follow up were assessed. The Expanded Disability Status Scale (EDSS), Kurtzke's Visual Functional System (KVS) and Wingerchuk’s Optic Nerve Impairment Scale (WONIS) were used to measure disability. Covariance analysis considering possible confounding factors in the prognosis, showed that NMOSD patients who presented isolated ON at disease onset developed poorer outcome than those who had ON associated with other neurological symptoms as the inicial manifestation of the disease. Interestingly, the data result of the two studies are complementary suggesting that the occurrence of ON as the inaugural symptom of NMOSD predicts poor visual outcome, especially when it occurs as an isolated symptom.